Paraphrasing Training Using Paraphraser Software as an Effort to Prevent Plagiarism - Perla Yualita; Sajodin Sajodin; Mia Anggi Anggraeni (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Currently, the phenomenon of plagiarism among students is still widespread. One effort to overcome plagiarism can be made through paragraph paraphrasing skills. Especially for high school (SMA) students who are the forerunners of students who are required to be productive in writing at least a final assignment publication. Therefore, it is deemed necessary to hold paragraph paraphrasing training using paraphraser software as an effort to prevent plagiarism at SMA Muhammadiyah 3 Bandung City. This PkM aims to increase students' knowledge about paraphrasing paragraphs through paraphraser software. Implementation methods: a) situation analysis for partners, b) pre-test implementation, c) provision of material, d) post-test implementation and activity evaluation. The PkM results show an increase in student's knowledge about paragraph paraphrasing through paraphraser software of 94.37 with a significance value of 0.000>0.05. Thus, in general, students are equipped with the knowledge to improve their ability to paraphrase paragraphs using paraphraser software. Apart from that, the students seemed to respond positively. This was proven by the enthusiasm and 100% attendance of the participants.